2023
DOI: 10.29303/jpm.v18i2.4783
|View full text |Cite
|
Sign up to set email alerts
|

Development of the uno chemical card game as a learning medium on the chemical bonding material for high school student

Abstract: This study aims to develop chemical uno cards as learning media in class X senior high school in chemical bonding materials that are valid and practical. This type of research is development research using the Plomp model. This research has three stages, namely (1) preliminary research, (2) prototyping stage, and (3) assessment phase. The subjects of this research consist of 5 chemistry lecturers at the Faculty of Mathematics and Science, Padang State University, two chemistry teachers, and 12 students at SMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…13 Games were also used to teach chemical bonding to grade 10 French students 14 and Indonesian high school students. 15 Although these studies utilized games in the teaching of the topic, they focused student's conception of chemical bonding and the validation and practicality of the games. No previous studies has found that the intervention improved academic achievement.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Games were also used to teach chemical bonding to grade 10 French students 14 and Indonesian high school students. 15 Although these studies utilized games in the teaching of the topic, they focused student's conception of chemical bonding and the validation and practicality of the games. No previous studies has found that the intervention improved academic achievement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other researchers also proposed a way of sequencing chemical bonding topics that would help students learn the concepts more effectively . Games were also used to teach chemical bonding to grade 10 French students and Indonesian high school students . Although these studies utilized games in the teaching of the topic, they focused student’s conception of chemical bonding and the validation and practicality of the games.…”
Section: Introductionmentioning
confidence: 99%